RELATIONSHIP OF NURSE WORKLOAD WITH RESPONSE TIME TO PATIENT’S HANDLING IN EMERGENCY INSTALLATION RSU PKU MUHAMMADIYAH BANTUL YOGYAKARTA. - siti saidah (Jurnal Keperawatan dan Kesehatan, 2020)
ABSTRACT Hospitals as a center for health services that must provide good quality services for patients by improving the quality of service. Emergency patient service were services that require immediate relief to prevent death and disability. One indicator of service quality was response time. There are several factors that affect response time, one of which is the high nurse workload. The purpose of this study to determine the relationship of nurse workload with response time to patient’s handling in Emergency Installation RSU PKU Muhammadiyah Bantul Yogyakarta. This research was conducted at emergency room RSU PKU Muhammadiyah Bantul Yogyakata, used cross sectional approach. The sample in this study amounted to 15 respondents taken in total sampling. The instrument used in this research is nurse workload questionnaire and observation sheet used stopwatch. The data analysis used kendalls tau by a computer programs SPSS. The result of the kendall tau show the significant 0,003, it means that ρ < α so there was relationship of nurse workload with response time to patient’s handling in Emergency Installation RSU PKU Muhammadiyah Bantul Yogyakarta. Keywords : Workload, Response time. ABSTRAK Rumah sakit sebagai pusat pelayanan kesehatan yang harus memberikan kualitas pelayanan yang baik bagi pasiennya dengan meningkatkan kualitas pelayanan. Pelayanan pasien gawat darurat adalah pelayanan yang memerlukan pertolongan segera untuk mencegah kematian dan kecacatan. Salah satu indikator pelayanan berupa response time. Terdapat beberapa faktor yang mempengaruhi response time salah satunya yaitu beban kerja perawat yang tinggi. Tujuan penelitian ini untuk mengetahui hubungan beban kerja perawat dengan response time pada penanganan pasien di IGD RSU PKU Muhammadiyah Bantul Yogyakarta. Penelitian ini dilaksanakan di IGD RSU PKU Muhammadiyah Bantul Yogyakarta, menggunakan pendekatan cross sectional. Sampel dalam penelitian ini berjumlah 15 responden yang diambil secara total sampling. Instrumen yang digunakan dalam penelitian ini adalah kuesioner beban kerja perawat dan lembar observasi menggunakan stopwatch. Analisa data menggunakan uji kendall tau dengan program komputer SPSS. Hasil uji kendall tau menunjukkan nilai signifikan 0,003, hal ini menunjukkan bahwa ρ < α ada hubungan antara beban kerja perawat dengan response time pada penanganan pasien di IGD RSU PKU Muhammadiyah Bantul Yogyakarta. Kata kunci : Beban Kerja, Response Time